MATERIALS FOR THE STUDY OF MACROSCOPIC FUNGI OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
The list of macroscopic fungi of Virahaioc mountains region of North Armenia is given. 168 species of macrofungi were revealed, 163 of which belong to division Basidiomycota, which includes class Basidiomycetes and subclass Holobasidiomycetidae, 14 orders, 30 families, 83 genus. 5 species belong to division Ascomycota, which is presented by 2 orders, 4 families and 5 genus. Among the revealed species 101 edible and 21 poisonous mushrooms were described.